Comparative assessment of HDI with Composite Development Index (CDI) - Ravi Prakash; Pulkit Garg (Insights into Regional Development)
This paper presents a novel approach to measure the human development, progress and growth of any country. The authors have developed an alternative index to the conventional 'HDI', named as 'Composite Development Index (CDI)' and have also presented an original approach to evaluate it quantitatively. The CDI integrates all the three (social, economic and environmental) aspects of sustainable development, along with peace and happiness. As proposed, the CDI is based on four parameters, i.e. Inequality adjusted HDI (IHDI), Scaled Green Index, Scaled Peace Index and Scaled Happiness Index, evaluated from globally accepted standard databases. Hence, the CDI is much more comprehensive and rational than the conventional HDI or GDP. The CDI values have been evaluated quantitatively for 126 countries of the world. Further, comparative assessment of the CDI has been done with the HDI for all the 126 nations. The results obtained have been startling as no country was even able to have a CDI score of 0.8 on a scale of 0.1 to 1. Switzerland had the highest CDI of 0.767. A country like Norway with the highest HDI of 0.953 had a CDI of only 0.742. On the other hand, countries like Costa Rica, Romania and Uruguay are in the top 20 nations in the CDI Ranking, much ahead of the countries like United Kingdom, France, and USA. The CDI can act as a single point of reference for policy-makers, governments and other development agencies, as it presents a consolidated picture of a country's development. Future course of action on the basis of the concept of CDI are also proposed. It can be concluded that efforts to have a high CDI (in comparison to a high GDP or HDI only) will pave the way forward for sustainable development and holistic progress for all the countries of the world.